Classification of file management in web based environment / Nazatul 'Izzati Zainal Abidin - Zainal Abidin, Nazatul 'Izzati (2009)
There is a lot of file management systems were introduced in order to digitalize the traditional file management. The file management should make the classifying or data mining However, the major problem of file management software and system is the data or file only will classify if users or policies require it to do so. Accordingly, this paper presents the classification of file management by identify the categories and type of files which available resources in a variety of formats and store in different table in a database using rules based method. The development of classification of file management system in'web based environment should automatically categorizing the upload file. The types of file that are usually used are defined and will support in CFM system. The system had been developed will classify the type of upload file into category using rule-based method. The system of Classification of File Management hope can be used efficiently as storing files and proper file management.